Optimalisasi Fintech Syariah untuk Inklusi Keuangan di Indonesia di Era Digital: Perspektif Ekonomi Islam. - Said, Muhammad (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2025)
This systematic literature review (SLR) investigates the optimization of sharia-compliant fintech to enhance financial inclusion in Indonesia, guided by Islamic economic principles. Analyzing 36 peer-reviewed articles from 2018 to 2024, the study employs a qualitative approach to explore trends, challenges, and opportunities. Findings reveal that sharia fintech, through innovations like peer-to-peer lending, crowdfunding, and e-wakaf, significantly improves access to financial services for unbanked populations and MSMEs. Key enablers include technological advancements, sharia compliance, and government support, while challenges involve regulatory ambiguity, low financial literacy, and public trust issues. The review underscores the importance of consumer preferences, literacy programs, and integration with sharia microfinance institutions in scaling adoption. Recommendations include robust regulatory frameworks, enhanced digital literacy initiatives, and collaborative ecosystems to ensure sustainable growth. This SLR contributes to the literature by synthesizing insights, identifying research gaps, and offering evidence-based strategies for policymakers and stakeholders to foster inclusive economic development in Indonesia’s digital era.